Different Types of Coagulase Are Associated With 28-Day Mortality in Patients With Staphylococcus aureus Bloodstream Infections - Karer, Matthias; Kussmann, Manuel; Ratzinger, Franz; Obermueller, Markus; Reischer, Veronika; Winkler, Heidemarie; Kriz, Richard; Burgmann, Heinz; Jilma, Bernd; Lagler, Heimo (Frontiers in Cellular and Infection Microbiology, 2020)
Background Staphylococcus aureus (S. aureus), a leading cause of bacteraemia and infective endocarditis, exploits the human coagulation system by using a wide range of specific virulence factors. However, the impact of these host-pathogen interactions on the outcome of patients with Staphylococcus aureus bacteraemia (SAB) remains unclear. Methods A total of 178 patients with S. aureus bacteraemia were included and analysed regarding bacterial factors (coa gene size, vWbp, clfA, clfB, fnbA, fnbB, fib) and clinical parameters. A stepwise multivariate Cox regression model and a Partitioning Around Medoids (PAM) cluster algorithm were used for statistical analysis. Results Patients’ risk factors for 28-day mortality were creatinine (OR 1.49, p<0.001), age (OR 1.9, p<0.002), fibrinogen (OR 0.44, p<0.004), albumin (OR 0.63, p<0.02), hemoglobin (OR 0.59, p<0.03) and CRP (OR 1.72, p<0.04). Five distinct bacterial clusters with different mortality rates were unveiled, whereof two showed a 2-fold increased mortality and an accumulation of specific coagulase gene sizes, 547-base pairs and 660-base pairs. Conclusions Based on the data obtained in the present study an association of coagulase gene size and fib regarding 28-day mortality was observed in patients with S. aureus bloodstream infections. Further animal and prospective clinical studies are needed to confirm our preliminary findings.